Digestion and Absorption of Milk Phospholipids in Newborns and Adults - Nilsson, Åke; Duan, Rui-Dong; Ohlsson, Lena (Frontiers in Nutrition, 2021)
Milk polar lipids provide choline, ethanolamine and polyunsaturated fatty acids which are needed for the growth and plasticity of the tissues in the suckling child. They may also inhibit cholesterol absorption by interaction with cholesterol during micelle formation and may have beneficial luminal, mucosal and metabolic effects in both the neonate and the adult. The milk fat globule membrane (MFGM) contains large proportions of sphingomyelin (SM), phosphatidylcholine (PC) and phosphatidylethanolamine (PE), and some phosphatidylserine (PS), phosphatidylinositol (PI) and glycosphingolipids. Large scale technical procedures are available for enrichment of MFGM in milk replacement formulations and in food additives. Pancreatic phospholipase A2 (PLA2) and mucosal phospholipase B digest glycero-phospholipids in the adult. In the neonate where these enzymes may be poorly expressed, pancreatic lipase related protein 2 probably has a more important role. Mucosal alkaline SM-ase and ceramidase catalyze the digestion of SM in both the neonate and adult. In the mucosa the sphingosine is converted to sphingosine-1-phosphate which is both an intermediate in the conversion to palmitic acid and a signaling molecule. This reaction sequence also generates ethanolamine. Here we summarize the pathways by which digestion and absorption pathways may be linked to biological effects of milk polar lipids. In addition to inhibition of cholesterol absorption and generation of lipid signals in the gut, utilization of absorbed choline and ethanolamine for mucosal and hepatic phospholipid synthesis, and acylation of absorbed lyso-PC with polyunsaturated fatty acids to chylomicron and mucosal phospholipids are important.